New data on the Harpacteinae of Turkey (Araneae, Dysderidae) - Kunt, Kadi̇r Boğaç; Özkütük, Recep Sulhi̇ (Zootaxa, 2023)
Eight new harpacteine species, Dasumia antalyaensis sp. nov. (♀), D. capacii sp. nov. (♂♀), D. yagmuri sp. nov. (♂♀), Harpactea bilecenoglui sp. nov. (♂♀), H. elvericii sp. nov. (♂♀), H. bilgenur sp. nov. (♂♀), H. kankilicorum sp. nov. (♂♀) and H. yanardagi sp. nov. (♂) are described from the eastern Mediterranean region of Turkey. Among three new species of Dasumia, D. antalyaensis sp. nov. and D. capacii sp. nov. are related to other congeners known from Turkey, while D. yagmuri sp. nov. is quite different from other known Dasumia species. Among five new species of Harpactea, three species; H. bilecenoglui sp. nov., H. elvericii sp. nov. and H. yanardagi sp. nov., due to their spiniform emboli, are close to H. sanctaeinsulae and H. isaurica, previously described from Turkey. Two other new speciess, H. bilgenur sp. nov. and H. kankilicorum sp. nov., exhibit the characteristics of the rubicunda species group like almost all of the Turkish Harpactea. However, these two new species have a more complex palp structure.